Redemption Road - Hart, John 1965-; Shepherd, Scott 1969 or 1970-; Macmillan Audio (Firm) ([New York] : Macmillan Audio, 2016)
A tour de force narrative from critically acclaimed, award-winning, New York Times bestselling author John Hart. Now Hart has written his most ambitious work to date. The novel features his first-ever female protagonist, Elizabeth Black, a recently probationed cop who must fight to keep her badge and stop an innocent man from being sent back to jail. There's more to Elizabeth than meets the eye, and the secrets she fiercely protects could be the source of her downfall. Add to this Hart's signature blend of a rich, atmospheric North Carolina setting, small town tension, family secrets, and the race to stop a serial killer.
Keywords: Policewomen -- Fiction; Secrecy -- Fiction; Judicial error -- Fiction; Serial murderers -- Fiction; Small cities -- Fiction; North Carolina -- Fiction; Thrillers (Fiction); Audiobooks